Recombinant single-cycle influenza virus with exchangeable pseudotypes allows repeated immunization to augment anti-tumour immunity with immune checkpoint inhibitors - Kandasamy, M; Gileadi, U; Rijal, P; Tan, TK; Lee, LN; Chen, J; Prota, G; Klenerman, P; Townsend, A; Cerundolo, V (eLife Sciences Publications, 2023)
Virus-based tumour vaccines offer many advantages compared to other antigen-delivering systems. They generate concerted innate and adaptive immune response, and robust CD8+ T cell responses. We engineered a non-replicating pseudotyped influenza virus (S-FLU) to deliver the well-known cancer testis antigen, NY-ESO-1 (NY-ESO-1 S-FLU). Intranasal or intramuscular immunization of NY-ESO-1 S-FLU virus in mice elicited a strong NY-ESO-1-specific CD8+ T cell response in lungs and spleen that resulted in the regression of NY-ESO-1-expressing lung tumour and subcutaneous tumour, respectively. Combined administration with anti-PD-1 antibody, NY-ESO-1 S-FLU virus augmented the tumour protection by reducing the tumour metastasis. We propose that the antigen delivery through S-FLU is highly efficient in inducing antigen-specific CD8+ T cell response and protection against tumour development in combination with PD-1 blockade.